PEMETAAN SPATIAL INDEKS PEMBANGUNAN MANUSIA DI JAWA TENGAH - Darsyah, Moh Yamin; Ajib, Gufron (Litbang PWM Jawa Tengah, 2023)
The Human Development Index (IPM) is a tool to measure development performance, especially human development carried out in a certain area at a certain time or specifically. This study examines HDI and the components of HDI, the data used is data on the values of HDI components for 35 districts/cities in Central Java Province. The variables used in this study were HDI (Y) as the dependent variable, AHH (X1), AMH (X2) and PPP (X3) as independent variables. The research examines the effect of spatial dependencies by using the area approach. Next is given the SEM application to identify how much influence the HDI constituent components can have on the HDI level in Central Java. The results of the study show that the distribution of HDI in Central Java Province has a regional grouping pattern. The results of modeling using SEM show lambda and all significant variables. The SEM model produces an AIC of 43.8540 which is better than the regression OLS method with an AIC of 45.6231.